Complex Open Pelvic Fracture in an 8-Year-Old Girl Treated With INFIX—A Case Study. (April 2019) - Rad, Darius; van Embden, Daphne; Bijlsma, Paulien; Bates, Peter
Abstract : We describe the case of an 8-year old female patient with an open pelvic fracture after being run over by a bus. Open pelvic injuries in pediatric patients are very rare and are associated with high mortality rates and long-term morbidity. In this case, a multidisciplinary surgical approach is described. The injuries include a complex pelvic ring fracture, which was treated with an internal external fixator, together with severe urogenital and soft-tissue injury. The internal external fixator, a surgical technique involving a temporary internal fixation device, is well described in adults, but has not been described in pediatric patients before. This case presentation shows the severity and complexity of the treatment of open pelvic fractures with severe associated injures. Albeit the treatment of her orthopaedic injuries has been successful so far, our patient unfortunately still suffers notable morbidity from her other injuries.